A zinc-catalyzed synthesis of 3-trifluoromethyl-4-trifluoroacetyl pyrazoles. (17th August 2022) - Hong, Biqiong; Ding, Xinzhi; Jiang, Mengfan; Qin, Lu; Lin, Zitong; Wu, Wei; Weng, Zhiqiang
Graphical abstract: Highlights: A method for synthesis of 3-trifluoromethyl-4‑trifluoroacetyl pyrazoles was developed. Various 3-trifluoromethyl-4‑trifluoroacetyl pyrazoles were isolated in moderate to excellent yields. A variety of functional groups were tolerated. Abstract: An efficient and general method for the synthesis of 3-trifluoromethyl-4‑trifluoroacetyl pyrazoles from the cycloaddition of sydnones with 1, 1, 1, 5, 5, 5-hexafluoropentane-2, 4-dione has been established. Using ZnI2 /bpy as a catalyst in THF, this protocol proved to be general to prepare a variety of 3-trifluoromethyl-4‑trifluoroacetyl pyrazoles in good yields. Utility of this method was demonstrated by further transformations of the trifluoroacetyl moiety providing convenient access to 3‑trifluoromethyl pyrazole-based carboxylic acid and alcohol derivatives.